ASSESSMENT OF IMMUNIZATION COVERAGE IN IRAN - Kiumarss Nasseri; Parviz Rezaii; Abolhassan Nadim (Tehran University of Medical Sciences, 1985)
In an effort towards complying with the WHO,s global policy of achieving Health For All by the year 2000 and also with the pledge made by the Government of Iran to that effect, a national headquarters has been set up to speed the implementation of the Expanded Programme on Immunization (EPI) in the country. This paper aims to report the results of evaluations made at various times since the beginning of the implementation of EPI in 1983.